Intervention of Public Policy on Behavior Change of Street Children in Indonesia - Yuri Maulydina; Lina Miftahul Jannah (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Poverty has a contribution to increase the number of street children then, street children are minors who maintain their lives on the streets. Many children stay in the street to make a living every day.  Because they are the country's most important resource, children, the policy and investment decisions made today will have significant implications for the country's future. The aim of this analysis is to analyze the implementation of public policy on behaviour change of street children in Indonesia. The method used in this analysis is Narrative Policy Analysis (NPA). NPA is a research method by using a narrative approach. Policies in dealing with street children in Indonesia are still top-down, so their implementation is measured through the indicators put forward by Edward III which include: communication, resources, arrangements, and bureaucratic structures. However, the needs of street children must also be known through a collaborative approach by combining top-down and bottom-up methods. In conclusion, direct individual support from government officials, the social community, and families also play a role in changing the behavior of street children. Policies that are repressive and do not understand the condition of street children tend not to change the behavior of street children. Policies should concern the real needs of street children and find out the vital causes of why they choose to live on the streets to prevent those condition. This analysis focused only on narrative policy to overcome children’s welfare. Thus, this analysis has a limit in comparing the condition of street children in various cities of Indonesia.